The islamic conception of justice - Khadduri, Majid 1908- (Johns Hopkins University Press, 1984)
The final chapter deals with the impact of Western notions of justice, with especial emphasis on the recurrence of fundamentalist movements such as the Islamic Revolution in Iran and the Muslim Brotherhood in Egypt, Pakistan, and other Islamic lands